MODIFICATION STUDY OF TWO TEETH DIFFERENCE SWING ROD MOVABLE TOOTH DRIVE BASED ON STATE OF TOOTH CONTACT - YI YaLi; ZHOU ZhengXiang; ZHOU YaZheng; ZHANG Shuang; GAO YunFei; JIN HeRong (Jixie qiangdu)
In order to improve the tooth surface contact state of the swinging rod,the elastic deformation of the center and the movable tooth meshing pair during the transmission process is analyzed.With minimum contact force as the target,the ring profile has medicated by combinion of equidistant and displacement modification,the influence of the modification on the contact force of meshing pair as well.Taking the ring-movable tooth engagement pair as an example,it is found that the tooth profile modification method based on the elastic deformation of the meshing pair reduces the maximum contact force and contact stress of the ring-movable tooth meshing pair by 10%,compared with the change of the meshing force in one push cycle before the trimming.By calculating the stiffness of the meshing pair,the average meshing stiffness after trimming is increased by 3%.The simulation of the virtual prototype was performed by Adams.The results show that the output speed is more stable after modification.The correctness of theoretical calculation is verified compared with Workbench finite element simulation.